2023
DOI: 10.1177/03635465231165297
|View full text |Cite
|
Sign up to set email alerts
|

Peroneus Longus Split Versus Semitendinosus Tendon Autograft Size: A Cross-sectional Study

Abstract: Background: The anterior half of the peroneus longus tendon (AHPLT) has been reported to be a suitable autograft for ligament reconstruction with low donor-site morbidity. However, clinical data on graft size are limited. Purpose: To determine (1) if there is any difference in size between the AHPLT and semitendinosus tendon (ST) and (2) whether anthropometric measurements can predict autograft size. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 128 consecutive patients schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Moderate, low and negligible correlation was reported in seven, nine and six studies, respectively. Eleven studies reported no significant correlation with graft diameter [4,6,10,29,39,40,43,45,48,51,69]. Cutoffs for predicting graft diameters above 8 mm ranged from 66 to 116 kg amongst four studies [15,56,63,70], while sensitivity and specificity ranged from 56% to 76.5% and 57.9% to 89% amongst two studies each, respectively [15,31].…”
Section: Anthropometric Parametersmentioning
confidence: 93%
See 4 more Smart Citations
“…Moderate, low and negligible correlation was reported in seven, nine and six studies, respectively. Eleven studies reported no significant correlation with graft diameter [4,6,10,29,39,40,43,45,48,51,69]. Cutoffs for predicting graft diameters above 8 mm ranged from 66 to 116 kg amongst four studies [15,56,63,70], while sensitivity and specificity ranged from 56% to 76.5% and 57.9% to 89% amongst two studies each, respectively [15,31].…”
Section: Anthropometric Parametersmentioning
confidence: 93%
“…Low and negligible correlations were reported in two studies and one study each. Five studies reported no significant correlation [6,43,45,51,69]. Cutoffs, sensitivities and specificities were not reported.…”
Section: Anthropometric Parametersmentioning
confidence: 96%
See 3 more Smart Citations